2019
DOI: 10.1007/s10047-019-01116-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of injury to the femoral blood vessels based on the extent of acetabular dysplasia in total hip arthroplasty

Abstract: We evaluated the course of the femoral blood vessels of patients with acetabular dysplasia. Patients were divided into five groups: those with Crowe type I, II, III, and IV dysplastic hips and those with normal hips. A computed tomography-based hip navigation software was used to measure the distance between the femoral blood vessels and the anterior pelvic wall in four axial planes located 10–40 mm proximal to the pelvic teardrop. In Crowe Groups I through IV, the distance was shortest at a point 20 mm proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As a result, the needle tip can be partially or transiently out of sight, increasing the risk of injury to vascular elements. In some individuals, the femoral artery and/or its branches can have an anomalous/tortuous course and lie close to the anterior hip joint capsule 15 . In this study, the transverse branch of the lateral circumflex femoral artery was discovered 8 mm anterior to the needle.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…As a result, the needle tip can be partially or transiently out of sight, increasing the risk of injury to vascular elements. In some individuals, the femoral artery and/or its branches can have an anomalous/tortuous course and lie close to the anterior hip joint capsule 15 . In this study, the transverse branch of the lateral circumflex femoral artery was discovered 8 mm anterior to the needle.…”
Section: Discussionmentioning
confidence: 48%
“…In some individuals, the femoral artery and/or its branches can have an anomalous/tortuous course and lie close to the anterior hip joint capsule. 15 In this study, the transverse branch of the lateral circumflex femoral artery was discovered 8 mm anterior to the needle. This distance may not be considered safe in terms of inadvertent injuries.…”
Section: Discussionmentioning
confidence: 67%
“…Concerning the correlation between the course of femoral blood vessels and the extent of acetabular dysplasia, Maeda et al [10] reported the mean shortest distances between vessels and the anterior pelvic wall in Crowe classification type I-IV to be 7.7, 6.7, 5.4, and 4.2 mm, respectively (The mean shortest distance in a normal hip was 7.5 mm.). Riouallon et al [5] proposed that defect of the anterior acetabular wall can make acetabular exposure more difficult and that absence of soft tissue between the femoral artery and the anterior acetabular wall can increase the likelihood of vessel injury caused by the anterior Hohmann retractor.…”
Section: Discussionmentioning
confidence: 99%